A Comparative Study of Speech Acts in EFL Textbook Life Today and Train of Thoughts For Student Grade XII of Curriculum Merdeka - Maguna Eliastuti; Tri Astuti; Roro Meifi Pitaloka; Vici Febriana (Politeknik Kampar, 2024)
Since it turns out the textbook's value as the primary focus of the curriculum, particularly in EFL environments cannot be understated. According to recent studies, even the most-latest textbooks provide insufficient amounts of pragmatic material to help learners enhance their pragmatic competence. Much more research regarding the extent and level of speaking acts must be conducted before future textbooks, specifically for EFL purposes. They are must able to deliver reliable and suitable examples of pragmatic information. Train for Thoughts and Life Today EFL Textbook are not yet comparable. To establish which of the two has more varieties of speech act categories, as well as the percentage and content of each. The study analyzes dialogue speech acts in two Indonesian EFL textbooks created by Kemendikbud and based on the Merdeka Curriculum. In this study, the descriptive qualitative method is applied. To examine each chapter of the dialogue section, the researcher implemented a table of checklists from Searle's (1979) Speech-Act Classification. Then, multiply the total number of speech acts categorised in each chapter by the percentage of the EFL Textbook. The two results were then compared.